2013
DOI: 10.1007/s00259-013-2395-x
|View full text |Cite
|
Sign up to set email alerts
|

Boosted selective internal radiation therapy with 90Y-loaded glass microspheres (B-SIRT) for hepatocellular carcinoma patients: a new personalized promising concept

Abstract: PurposeTo evaluate the impact of dosimetry based on MAA SPECT/CT for the prediction of response, toxicity and survival, and for treatment planning in patients with hepatocellular carcinoma (HCC) treated with 90Y-loaded glass microspheres (TheraSphere®).MethodsTheraSphere® was administered to 71 patients with inoperable HCC. MAA SPECT/CT quantitative analysis was used for the calculation of the tumour dose (TD), healthy injected liver dose (HILD), and total injected liver dose. Response was evaluated at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
155
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(168 citation statements)
references
References 28 publications
9
155
0
4
Order By: Relevance
“…All published studies found a dose-efficacy correlation: with resin spheres, both in HCC [31] and in CRC metastases [32,33], and with glass spheres in HCC [34,35]. Statistically significant differences in the most important oncological end points, i.e., overall survival, progression-free survival and time to progression, were correlated with lesion absorbed doses higher or lower than about 200 Gy with glass spheres in HCC [36,37]. As regards radio-induced liver toxicity, Sangro et al [38] found that the threshold for RE-induced liver disease (REILD) with resin spheres is an activity greater than 0.8 GBq/L, which corresponds to 50 Gy kg/ GBq 9 0.8 GBq/1 kg = 40 Gy mean absorbed dose to non-tumoral parenchyma.…”
Section: Treatment Planning With 99m Tc-maa Spectmentioning
confidence: 99%
“…All published studies found a dose-efficacy correlation: with resin spheres, both in HCC [31] and in CRC metastases [32,33], and with glass spheres in HCC [34,35]. Statistically significant differences in the most important oncological end points, i.e., overall survival, progression-free survival and time to progression, were correlated with lesion absorbed doses higher or lower than about 200 Gy with glass spheres in HCC [36,37]. As regards radio-induced liver toxicity, Sangro et al [38] found that the threshold for RE-induced liver disease (REILD) with resin spheres is an activity greater than 0.8 GBq/L, which corresponds to 50 Gy kg/ GBq 9 0.8 GBq/1 kg = 40 Gy mean absorbed dose to non-tumoral parenchyma.…”
Section: Treatment Planning With 99m Tc-maa Spectmentioning
confidence: 99%
“…In this study, response rate was significantly higher when using personalized dosimetry, at 86 % compared to only 55 % while using the standard dosimetric approach aiming to deliver 120 ±20 Gy to the treated liver, regardless of the TD (p=0.001) [11]. In a cohort of 41 PVT patients treated with personalized dosimetry, with intensification in 37 %, the median OS was 18 months [95 % confidence interval (CI) 11-25 months], highly impacted by TD.…”
mentioning
confidence: 92%
“…ATD exceeding 205 Gy has also been reported as the only parameter associated with response on multivariate analysis, correlating with OS, especially in PVT patients [10]. In the case of unilobar treatment, HILD alone was not correlated with liver toxicity, yet a HILD>120 Gy combined with a small hepatic reserve (<30 %) highly correlated with permanent liver toxicities (p<0.0001) [11].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…They determined a threshold dose of 205 Gy which enabled a response prediction with 91% accuracy and 100% sensitivity [108]. Using this threshold in a cohort of 71 patients, the group detailed 17 patients who underwent treatment intensification to achieve D T > 205 Gy while maintaining D NL <120 Gy [109]. They show an OS of 11.5 months and 23.2 months for D T < 205 Gy and > 205 Gy respectively.…”
Section: Dose Response Relationshipmentioning
confidence: 99%